2019
DOI: 10.1002/ijfe.1750
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic correlation and volatility spillovers across Chinese stock and commodity futures markets

Abstract: This paper examines the return links and volatility transmission between Chinese stock and commodity futures markets and draws implications for portfolio risk management. To these ends, we consider three vector autoregression‐multivariate generalized autoregressive conditional heteroskedasticity‐class models with which to model volatilities and conditional correlations between Chinese stock and three commodity futures markets. Our empirical results reveal evidence of return linkage and volatility transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In particular, all average DCCs are below 15%, whereas DCC for gold is the lowest one and is around 11%. This preliminary finding indicates that precious metals could successfully serve as a diversification tool in a portfolio with corn, which is in line with some recent papers (Mirović et al 2017;Kang and Yoon 2019). In addition, all DCC plots have the same distinctive feature, and that is the rise of DCCs around the period of global financial crisis (GFC).…”
Section: Resultssupporting
confidence: 89%
“…In particular, all average DCCs are below 15%, whereas DCC for gold is the lowest one and is around 11%. This preliminary finding indicates that precious metals could successfully serve as a diversification tool in a portfolio with corn, which is in line with some recent papers (Mirović et al 2017;Kang and Yoon 2019). In addition, all DCC plots have the same distinctive feature, and that is the rise of DCCs around the period of global financial crisis (GFC).…”
Section: Resultssupporting
confidence: 89%
“…Studies have shown that the heterogeneous structure of PAR 33,2 the commodities market provides investors with the benefits of portfolio diversification (Öztek and Öcal, 2017;Maghyereh et al, 2019;Salisu et al, 2020). The existing literature has measured the dynamic interdependence between financial and commodity markets by applying various measures of connectedness (Shahzad et al, 2017;Corbet et al, 2018;Kang and Yoon, 2020;Zeng et al, 2020). Consequently, our paper contributes to the recent literature that examines the impact of COVID-19 on various financial markets (Akhtaruzzaman et al, 2020;Bouri et al, 2020;Corbet et al, 2020;Sharif et al, 2020;Yarovaya et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Singhal et al (2019) found that the usage of oil as inputs in the production process has a significant impact on stock market returns in Mexico, and it occurs through the exchange rate channel as the Mexican economy is heavily dependent upon exports of various industrial products and commodities, including crude oil. A study by Kang and Yoon (2019) presented evidence of unidirectional return and volatility transmission between the Chinese stock market and commodity futures, implying that commodity futures contribute to the role of price discovery in their equity markets.…”
Section: Literature Reviewmentioning
confidence: 99%